Perkembangan Pasar Ikan Di Tamboo, 2017-2020 - Sutrisno Mohamad; Asmun Wantu; Andris K. Malae (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to find out the development of the fish market in Tamboo Village in 2017-2020. At the beginning of its establishment, the fish market in Tamboo Village did not have complete facilities. In 2017 the market facilities in Tamboo Village still used makeshift tools. In 2018, the community received assistance from the government in the form of fish stalls using cement and clean water. This assistance, although not comprehensive, can help the community's trading activities. In 2019 the market position or market location was moved back to its initial position, which was near the beach. The relocation of the market caused differences of opinion between the community and the village government. The community and the village government have made an agreement on the location of the permanent market in the new location and the market facilities have been reopened. The impact of the agreement is that trading activities run normally. Market developments in 2020 are marked by concreting and clean water. The number of public facilities that support selling activities is adequate and complete. Los as a place to sell can accommodate various traders. The market has foremen and janitors. Keywords: Fish market, fishermen, facilities.